PENGEMBANGAN WEBSITE INTERAKTIF BERBASIS NANO-LEARNING UNTUK PENGUATAN KOMPETENSI PEDAGOGIK DIGITAL GURU SD MUHAMMADIYAH INOVATIF MERTOYUDAN - Fatkhussarifin, Fatkhussarifin; Wicaksono, Dirgantara (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This research aimed to develop an interactive website based on nano learning as a digital pedagogical tool to strengthen the digital pedagogical competence of elementary school teachers. The development model followed the Dick and Carey instructional design framework, which consists of ten systematic stages ranging from goal identification, instructional analysis, learner analysis, to formative and summative evaluations. The product was tested through expert validation and field trials involving 10 teachers and 30 students at SD Muhammadiyah Inovatif Mertoyudan. Data collection techniques included interviews, observations, questionnaires, and pre-test/post-test. The website allowed teachers to independently create and share nano learning content in the form of short videos, fun facts, and interactive quizzes. Expert validation showed good to very good feasibility (average scores of 4.17 and 4.33), while user trials showed positive feedback on usability and content attractiveness. Effectiveness was measured using a Likert-scale perception test from students, indicating an increase in the average score from 3.22 to 4.38 after using the website. The findings indicate that nano learning-based digital content can be a practical and effective solution for improving digital pedagogy in schools.